2011
DOI: 10.3996/092010-jfwm-034
|View full text |Cite
|
Sign up to set email alerts
|

Seed Abundance for Waterfowl in Wetlands Managed by the Illinois Department of Natural Resources

Abstract: Managed wetlands on public lands in Illinois, United States, provide foraging habitats for migrating and wintering waterfowl. However, few studies have estimated abundances of waterfowl foods in mid-migration regions of North America, yet such information is needed to inform management and conservation decision-making. During 2005-2007, we used a multistage sampling design to estimate moist-soil plant seed production (kg/ha, dry mass) and energetic carrying capacity at sites managed by the Illinois Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 22 publications
4
35
1
Order By: Relevance
“…Our estimate of plant food densities in moist‐soil wetlands in western Tennessee (633.5 kg/ha) is similar to estimates reported in the Mississippi Alluvial Valley (550 kg/ha; Kross et al ), the Upper Mississippi River Valley/Great Lakes regions (377–570 kg/ha; Brasher et al ), and the Illinois River Valley (691.3 kg/ha; Stafford et al ). Moreover, our estimate is considerably greater than was reported in palustrine emergent wetlands in the Upper Midwest during spring (208 kg/ha; Straub et al ) and in Wetland Reserve Program easements in the Mississippi Alluvial Valley during winter (263.5 kg/ha; Olmstead et al ).…”
Section: Discussionsupporting
confidence: 86%
“…Our estimate of plant food densities in moist‐soil wetlands in western Tennessee (633.5 kg/ha) is similar to estimates reported in the Mississippi Alluvial Valley (550 kg/ha; Kross et al ), the Upper Mississippi River Valley/Great Lakes regions (377–570 kg/ha; Brasher et al ), and the Illinois River Valley (691.3 kg/ha; Stafford et al ). Moreover, our estimate is considerably greater than was reported in palustrine emergent wetlands in the Upper Midwest during spring (208 kg/ha; Straub et al ) and in Wetland Reserve Program easements in the Mississippi Alluvial Valley during winter (263.5 kg/ha; Olmstead et al ).…”
Section: Discussionsupporting
confidence: 86%
“…Partial river reconnection at the Merwin Preserve created high water levels during spring and early summer, followed by a progression from stagnant, warm waters to dry conditions during the post-flood summer that greatly altered vegetation conditions. Late-summer drawdowns exposed mudflats important for migrating shorebirds (Smith et al, 2012) and produced moist-soil vegetation for migrating waterfowl (Stafford et al, 2011) that also resulted in the loss of nearly all submersed and floating-leaf aquatic vegetation. Similar elimination of aquatic vegetation from fluctuating water levels during the growing season has occurred among backwater lakes and wetlands with partial connectivity to the Illinois River (Bellrose et al, 1983;Moore et al, 2010;Stafford et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To estimate a critical food density for comparison with GUDs, we followed the process outlined by van Gils et al () using published functional responses, daily energy requirements, and time‐activity budgets. We estimated the critical intake rate for dabbling ducks using the functional response of green‐winged teal Anas crecca (van Eerden and Munsterman ) and published estimates of energy requirements and foraging rates of dabbling ducks (Stafford et al ). We assumed 7.9–11.3 h were available to ducks for foraging based on diurnal and nocturnal foraging rates of Jones et al () and means across species of dabbling ducks from Jorde and Owen ().…”
Section: Methodsmentioning
confidence: 99%
“…We assumed 7.9–11.3 h were available to ducks for foraging based on diurnal and nocturnal foraging rates of Jones et al () and means across species of dabbling ducks from Jorde and Owen (). We used a previously estimated constant for daily energetic requirements of dabbling ducks in the Illinois River valley (337 kcal day –1 ; Stafford et al ) and mean true metabolizable energy for dabbling ducks consuming millet and rice (2.79 kcal g –1 ; Kaminski et al ). We assumed the functional response would be similar for millet and rice, given that both would have been classified as small food items by Fritz et al (), who found type I and type II function responses in mallards A. platyrhynchos were similar for small foods.…”
Section: Methodsmentioning
confidence: 99%